THE TEXT OF KRAMAT KAREM SONG GAMBANG KROMONG BETAWI A HERMENEUTIC REVIEW - Sri Repelita, Malona; Sudirga, I Komang; Arshiniwati, Ni Made; Sustiawati, Ni Luh (International Journal of Multidisciplinary Research and Literature, 2026)
Kramat Karem is a song from Betawi cultural heritage whose lyrics tell the story of the tsunami event as a result of the eruption of Mount Krakatau in 1883 in the Sunda Strait, Indonesia. The lyric contains stories, descriptions of disaster, and the traditional local wisdom that accompanies them. Kramat Karem lyric have changed over the generations, the singer's interpretation is influenced by historical experience and the background context. From era to era, the meaning does not represent the original intend of the author anymore. This study aims to examine the the singer interpretation from hermeneutic approach and the function of socializing the local wisdom. This research used qualitative method and were analyzed using a hermeneutic approach as a big frame to examine changes of the text in the contemporary Kramat Karem song. The data were collected through literature studies, interviews, records from social media and observations in the community. This study is expected to produce recommendations for Betawi's ethnic to learn and appreciate local wisdoms in gambang kromong songs. In addition, the results of this study also become a trigger for Betawi society to strengthen the Betawi tradional Culture as a medium of communication and social integration.